2014
DOI: 10.1016/j.envpol.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Riverbank filtration potential of pharmaceuticals in a wastewater-impacted stream

Abstract: Pharmaceutical contamination of shallow groundwater is a substantial concern in effluent-dominated streams, due to high aqueous mobility, designed bioactivity, and effluent-driven hydraulic gradients. In October and December 2012, effluent contributed approximately 99% and 71%, respectively, to downstream flow in Fourmile Creek, Iowa, USA. Strong hydrologic connectivity was observed between surface-water and shallow-groundwater. Carbamazepine, sulfamethoxazole, and immunologically-related compounds were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 50 publications
2
42
2
Order By: Relevance
“…The fluoroquinolones ciprofloxacin and enrofloxacin were the only APIs detected above quantification levels in the upstream sample (54.3 and 185.6 ng/L respectively), potentially due to upstream agricultural pressures or other urban sources (e.g., leaking sewer lines or septic systems). The total API concentration was lowest upstream of the WWTP (239.9 ng/L), highest in the WWTP effluent (10,373 ng/L) and attenuated (from 5561.5 to 3699.4 ng/L) with increasing distance downstream from the WWTP outfall ( Figure 5) as one would expect in an effluent-dominated system [25]. At the time of sampling, 55% of Muddy Creek flow downstream from the WWTP consisted of sewage plant effluent.…”
Section: Concentrations Of Studied Apis In Muddy Creekmentioning
confidence: 74%
“…The fluoroquinolones ciprofloxacin and enrofloxacin were the only APIs detected above quantification levels in the upstream sample (54.3 and 185.6 ng/L respectively), potentially due to upstream agricultural pressures or other urban sources (e.g., leaking sewer lines or septic systems). The total API concentration was lowest upstream of the WWTP (239.9 ng/L), highest in the WWTP effluent (10,373 ng/L) and attenuated (from 5561.5 to 3699.4 ng/L) with increasing distance downstream from the WWTP outfall ( Figure 5) as one would expect in an effluent-dominated system [25]. At the time of sampling, 55% of Muddy Creek flow downstream from the WWTP consisted of sewage plant effluent.…”
Section: Concentrations Of Studied Apis In Muddy Creekmentioning
confidence: 74%
“…[25] This could indicate intraspecific differences. However, sewage effluents generally contain a mixture of various complex organic compounds including other contaminants and other pharmaceuticals and personal care products, [3,17,25,34] which may influence the bioconcentration potential of individual pharmaceuticals. [35] Furthermore, it is important to remember that differences in temperature and water properties, [36] and in fish size, age and condition [6] may complicate comparisons across species and studies because these factors have the potential to influence the level of bioconcentration.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to often high prescription rates, and limited removal of excreted bioactive forms in wastewater treatment plants, various psychiatric pharmaceuticals end up in aquatic environments. [1][2][3][4][5] There, exposure to those pharmaceutical residues may affect aquatic wildlife [6][7][8] because many biological systems (e.g. enzymes, receptors) that pharmaceuticals interact with are evolutionarily conserved across a wide range of species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have looked at sorption of ibuprofen and reported lower soil sorption coefficients for this acidic PhAC (Loffler et al, 2005) especially as compared to basic PhACs (Yamamoto et al, 2009). There is evidence that PhACs can be attenuated during transport by soil materials into groundwater from surface water (Bradley et al, 2014). Degradation occurring in the soil environment has been observed to result in PhAC transformation products due to chemical transformations of the parent compound (Dodgen et al, 2014;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 92%